Comparative study between hysteroscopy and transvaginal ultrasound in evaluation of unexplained infertility - Abd-Ela; Mahmoud EL-Rashidy; Mahmoud Badawy; Hend Ali Mohammad (Wolters Kluwer Medknow Publications, 2021)
Background Three types of uterine factors have been implicated in infertility: leiomyomas, endometrial polyps, and intrauterine adhesions. Mechanisms of infertility have not clearly been elucidated; however, the end result is decreased endometrial receptivity and reduced likelihood of embryo implantation. Transvaginal sonography is a sensitive method for the evaluation of the uterine masses and abnormalities. Objective To evaluate the diagnostic accuracy of transvaginal ultrasonography in detection of intrauterine abnormalities compared with hysteroscopy in women with history of unexplained infertility. Patients and methods The study was conducted in infertility clinic of Al-Azhar Assiut University Hospital. A total of 30 cases were included in the study during the period between August 2018 and March 2019. The chief complaint of patients was unexplained infertility. All candidates underwent transvaginal ultrasound, and the uterus was examined in longitudinal and transverse planes (two-dimensional transvaginal ultrasound) and the three-dimensional transvaginal ultrasound), and hysteroscopic examination was done for all cases using general anesthesia. Results In our current study, using transvaginal ultrasound, we diagnosed 28 cases with abnormalities (nine intrauterine adhesions, seven fibroids, six polyps, four irregular endometrium, one case of endometritis, and one case of septum). By hysteroscopy, 27 cases were confirmed to have abnormalities (11 intrauterine adhesions, five fibroids, seven polyps, two endometritis, and two cases of septum). Conclusion Routine use of transvaginal sonography (two dimensional and three dimensional) in diagnosing uterine cavity abnormalities is satisfactory and consequently is becoming a basic tool in investigating infertile patients. Hysteroscopy which is the gold standard in investigating the uterine cavity should be used to confirm the findings of transvaginal sonography and also when transvaginal sonography gives doubtful results.